ANÁLISE DOS MÉTODOS DE MARCAÇÃO EM VERTEBRADOS – A EXPERIÊNCIA DO ZOOLÓGICO DO PARQUE ESTADUAL DOIS IRMÃOS, RECIFE, PERNAMBUCO - Souza, Dênisson da Silva e; Siqueira, Daniel Barreto; Albuquerque, Luciana Carla Ramehde; Silva, Márcio André da; Caldas, Bárbara Lins; Guarnieri, Miriam Camargo; Moura, Geraldo Jorge Barbosa de (Revista Nordestina de Zoologia, 2011)
Keeping wild animals in captivity is very important in species conservation for it is one proposed objective of the new concept of a modern zoo. In this way it becomes essential to know, control and monitor the specimens in these environments. An important tool for achieving these requirements is the individual identification, being necessary to monitor the clinical and genetic history of individuals, enabling a more efficient veterinary and biological management, but also to conform legislation of environmental regulations. This paper describes the individual identification systems deployed in animals of the Dois Irmãos State Park - PEDI, Recife-PE. The used methods were tattooing, microchip implantation and banding, while each technique was chosen considering the practicality, efficiency, cost-benefit, durability and adaptability as well as the biology of the target specimen, their sensitivity to capture and containment, and individual behavior. In the period of study 504 animals were marked which includes 121 birds, 323 “reptiles” and 66 mammals. The markings were very effective since few arising problems from the procedures were observed. Tattooing turned out to be the most time consuming method for application as well as for reading. Although it is restricted to birds, banding served well the needs of the institution while providing a low cost, durability and practicality of implementation besides the method is painless to specimens. Having a lower implementation cost, the microchip method is representing the most advantageous method in terms of durability, reliability in identification and practical application. For the PEDI, the microchip method showed the best cost-effectiveness for all groups of "reptiles" and mammals, while the banding method was more efficient for the group of birds.